2006
DOI: 10.1016/j.neurobiolaging.2005.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on atrophy rates of entorhinal cortex and hippocampus

Abstract: The effects of age, subcortical vascular disease, apolipoprotein E (APOE) 4 allele and hypertension on entorhinal cortex (ERC) and hippocampal atrophy rates were explored in a longitudinal MRI study with 42 cognitively normal (CN) elderly subjects from 58 to 87 years old. The volumes of the ERC, hippocampus, and white matter hyperintensities (WMH) and the presence of lacunes were assessed on MR images. Age was significantly associated with increased atrophy rates of 0.04 ± 0.02% per year for ERC and 0.05 ± 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
151
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(179 citation statements)
references
References 61 publications
24
151
3
1
Order By: Relevance
“…However, opposite results were also observed. Indeed, Du et al, reported that the APOE ε4 allele did not contribute to increase the atrophy rate of the hippocampus and of the enthorinal cortex in a cross-sectional study (34). Similarly, in a 1-year volumetric follow-up study, Jack et al (35) reported that the hippocampal volume decrease did not differ in normal subjects carrying with different APOE alleles.…”
Section: Discussionmentioning
confidence: 94%
“…However, opposite results were also observed. Indeed, Du et al, reported that the APOE ε4 allele did not contribute to increase the atrophy rate of the hippocampus and of the enthorinal cortex in a cross-sectional study (34). Similarly, in a 1-year volumetric follow-up study, Jack et al (35) reported that the hippocampal volume decrease did not differ in normal subjects carrying with different APOE alleles.…”
Section: Discussionmentioning
confidence: 94%
“…One of the major factors associated with hippocampal changes is age. The age association has been demonstrated in several studies with cross-sectional (Lim et al, 1990, Coffey et al, 1992, Pfefferbaum et al, 1994, Sullivan et al, 1995, De Leon et al, 1997, Schuff et al, 1999, Jernigan et al, 2001, Scahill et al, 2003, Sullivan et al, 2005 and longitudinal (Jack et al, 1998, Scahill et al, 2003, Raz et al, 2004b, Du et al, 2006 designs. Recent research based on magnetic resonance imaging (MRI) has also demonstrated that a spatial mapping method could enhance the detection of the subtle changes in volumetric information and the understanding of age effects on specific regions of hippocampi (Janke et al, 2001, Wang et al, 2003, Thompson et al, 2004, Chetelat et al, 2005.…”
Section: Introductionmentioning
confidence: 85%
“…However, these findings in healthy subjects have been inconsistent. Some studies revealed that age was not significantly related to the volume reduction of the hippocampus (Sullivan et al, 1995, Sullivan et al, 2005; others obtained the opposite results (Lim et al, 1990, Convit et al, 1995, De Leon et al, 1997, Jernigan et al, 2001, Scahill et al, 2003, Raz et al, 2004a, Raz et al, 2004b, Du et al, 2006. The discrepancies in the results of these reports might be due to differences in the segmentation of anatomical regions, or in the age range of the subjects studied.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Jokinen et al, 2012; Kramer et al, 2007]. However, some researchers have discovered no change‐change correlations between brain volumes and cognitive abilities: Charlton et al [2010] found no significant correlation between declines in brain volume and working memory in a two‐year longitudinal study of 84 healthy adults aged 50 to 90 years (see also Du et al, [2006]), which may reflect the shorter duration of follow‐up, age heterogeneity, and smaller sample.…”
Section: Introductionmentioning
confidence: 99%